If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -117 + -10x = 9x + 1 + 6 Reorder the terms: -117 + -10x = 1 + 6 + 9x Combine like terms: 1 + 6 = 7 -117 + -10x = 7 + 9x Solving -117 + -10x = 7 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. -117 + -10x + -9x = 7 + 9x + -9x Combine like terms: -10x + -9x = -19x -117 + -19x = 7 + 9x + -9x Combine like terms: 9x + -9x = 0 -117 + -19x = 7 + 0 -117 + -19x = 7 Add '117' to each side of the equation. -117 + 117 + -19x = 7 + 117 Combine like terms: -117 + 117 = 0 0 + -19x = 7 + 117 -19x = 7 + 117 Combine like terms: 7 + 117 = 124 -19x = 124 Divide each side by '-19'. x = -6.526315789 Simplifying x = -6.526315789
| (x^2-10x)*(64-x^2)=0 | | 2x-2x/7=x/4+5 | | 5x=77-4x | | 18x^2x20x^11/12x^8 | | 1+8c+12c^2=0 | | 22/63/2 | | 9x+4=4x+34 | | x^2-7x-228=0 | | 9x+3=-7+6x+22 | | -(p-623)/2=50 | | -(p-623)=50 | | 1/4X48 | | -p+623/2=50 | | (2x-3)*sqrt^3(2x^2-5x+2)=0 | | -2y+5=-7 | | 5n-10=7n+13 | | 12x-2=12x-42 | | 3y^4-11y^2-20= | | -x^3+2x^2+25X-50=0 | | mx-2=0 | | -x^3-x^2+4x+1=0 | | -x^3-9x^2+25x+20=0 | | x^3+9x^2-25x-20=0 | | -35z^2-13z+12= | | x^3-37x-52=0 | | 1.4=.14xn | | (m-2)x^2+(3m-5)x+3=0 | | 0*z=-1 | | 1+1-(1-x)-(1-x)-(1-x)=0 | | (1-x)(1-x)(1-x)=0 | | (1-x)(1-x)(1-x)+1+1-(1-x)-(1-x)-(1-x)=0 | | 3/4*(5*x-2)-1/2*(3*x+4)=1 |